2004
DOI: 10.1016/s0002-9440(10)63117-3
|View full text |Cite
|
Sign up to set email alerts
|

pp32 Reduction Induces Differentiation of TSU-Pr1 Cells

Abstract: pp32 (ANP32A) is a nuclear phosphoprotein expressed as a nonmutated form in self-renewing cell populations and neoplastic cells. Mechanistically, pp32 may regulate pathways important in the process of differentiation as part of separate complexes inhibiting histone acetylation and regulating immediate-early and cytokine mRNA stability. Prostatic adenocarcinomas express pp32 in a differentiation related manner-well-differentiated tumors express lower levels of pp32 than poorly differentiated tumors. In benign p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 26 publications
1
25
1
Order By: Relevance
“…49 Although these data seem contradictory to our findings the two data sets are difficult to compare because the authors did not assess the effect of SET overexpression in TSU-Pr1 cells. In addition, the effects of SET might be different in different cell types.…”
Section: Set Induces Dendritic Cell-like Differentiation Of U937 Cellscontrasting
confidence: 92%
“…49 Although these data seem contradictory to our findings the two data sets are difficult to compare because the authors did not assess the effect of SET overexpression in TSU-Pr1 cells. In addition, the effects of SET might be different in different cell types.…”
Section: Set Induces Dendritic Cell-like Differentiation Of U937 Cellscontrasting
confidence: 92%
“…However, in some cancers, pp32 is highly expressed, such as highly malignant prostatic adenocarcinomas. 27,28 A fairly recent study has shown hyperphosphorylated Rb, the retinoblastoma gene product, associates with pp32. 29 Rb is an important tumor suppressor and cell cycle regulator, that controls the G1/S transition, whose active form is a hypophosphorylated state.…”
Section: Discussionmentioning
confidence: 99%
“…It accelerates caspase activation by stimulating the apoptosome, but the in vivo significance of this is unclear. In contradistinction to its pro-apoptotic and transformation inhibition functions, pp32 is highly expressed in cancer (37). In fact, pp32 is more highly expressed in highly malignant prostatic adenocarcinomas with Gleason scores of Ն5 than in clinically indolent tumors with Gleason scores of Ïœ5 (38).…”
mentioning
confidence: 99%